Investigation of the size effect of graphene nano-platelets (GnPs) on the anti-corrosion performance of polyurethane/GnP composites. Issue 31 (9th May 2018) - Um, Jun Geun; Jun, Yun-Seok; Alhumade, Hesham; Krithivasan, Hariharan; Lui, Gregory; Yu, Aiping
Abstract : In this article, polyurethane/graphene nano-platelet (PU/GnP) composites were fabricated via planetary centrifugal mixer (PCM) and cast on polyethylene terephthalate (PET) and copper substrates. Abstract : In this article, polyurethane/graphene nano-platelet (PU/GnP) composites were fabricated via planetary centrifugal mixer (PCM) and cast on polyethylene terephthalate (PET) and copper substrates. Four different grades of GnP are used to investigate the effect of GnP size on the anti-corrosion performance of the composites. Tafel, Nyquist, and Bode plots are used to quantify and compare the anti-corrosion performance of the composites, and these plots are obtained by electrochemical analysis. In addition to the anti-corrosion performance, mechanical properties and morphologies of the composites are analyzed. Various parameters indicating the anti-corrosion performance illustrate that smaller size of GnP in the composites shows higher anti-corrosion performance on copper substrate. The results show that the smaller size of GnP is not only uniformly dispersed within PU, but also offers a high surface area which helps construct an efficient filler pathway that suppresses the diffusion of a corrosive agent into the polymer matrix. Nevertheless, mechanical properties of the composites are partially improved. Essentially, this study demonstrates that the size of GnP plays a central role in determining the anti-corrosion performance of PU/GnP composites.